PHYTOCHEMICAL CONSTITUENTS AND PHARMACOLOGICAL ACTIVITIES OF Kigelia africana AND Mansoa alliacea - A COMPREHENSIVE REVIEW - Venkataraman, Sowmyalakshmi; Srilakshmi, Gunda (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: The focus of the present review is to compile the different phytochemical constituents and pharmacological activities of bignoniaceous plants, namely Kigelia africana and Mansoa alliacea. Objective: Medicinal plants are routinely used in clinical practice for the treatment of various diseases of human beings over thousands of years across the world. In rural areas of the developing countries, they are still used in practice due to the easy availability of the medication. The main objective of this work is to explore the phytochemical studies and biological activities of plants belonging to Bignoniaceae family. Methods: The present study also discusses about the different phytochemical constituents of K. africana and M. alliacea that were isolated and characterized using various analytical methods. Different extracts of these plants were subjected to different in vitro anticancer, analgesic, antimicrobial, and antimalarial activities using earlier reported methods were also discussed. Results: K. africana is commonly referred to as sausage or cucumber tree due to its huge sausage or cucumber-like fruit. These plants find application as traditional medicine for treating several ailments such as malignant tumor, ulcer, aging, and malaria among others. It is conjointly used for the treatment of reproductive organ infections, renal ailments, dizziness, epilepsy, sickle cell disease, depression, metabolism disorders, skin grievance, leprosy, impetigo, helminthic infections, athlete’s foot, tumors, etc. These plant extracts have also been used as a cosmetic by enhancing the collagen action and thus exhibit antiaging properties. Conclusion: The present study attempts to provide collective information on various phytochemical constituents and pharmacological actions of K. africana and M. alliacea belonging to Bignoniaceae. This review in its present form is believed to help the researchers to provide adequate information about the chemical constituents and biological uses of these plants.